2017
DOI: 10.1038/s41598-017-16091-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis shows that RNase G plays a global role in the stability of mRNAs in Stenotrophomonas maltophilia

Abstract: Gene expression is determined by critical processes such as RNA synthesis and degradation. Ribonucleases participate in the coordinated and differential decay of messenger RNAs. We describe a suitable method of normalization and calculation of mRNAs half-life values quantified by RNA-Seq. We determined the mRNA half-lives of more than 2000 genes in Stenotrophomonas maltophilia D457 and in an isogenic RNase G deficient mutant. Median half-lives were 2,74 and 3 min in the wild-type and the rng-deficient strain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…An E. coli transcriptome-wide mRNA half-life study by a different group reported that the rate of mRNA degradation had a very weak positive correlation with mRNA abundance for both exponential phase ( R 2 = 0.07) and stationary phase ( R 2 = 0.19) ( Chen et al, 2015 ), in contrast to other E. coli studies ( Bernstein et al, 2002 ; Esquerre et al, 2014 , 2015 ). In Bacillus cereus , mRNA half-life had a positive correlation with expression level ( Kristoffersen et al, 2012 ), while in Stenotrophomonas maltophilia and Chlamydia trachomatis trachoma and lymphogranuloma venereum biovars no correlations were found ( Bernardini and Martinez, 2017 ; Ferreira et al, 2017 ). In M. smegmatis , induced overexpression of dCas9 (in the absence of a gene-targeting sgRNA) did not alter its half-life in log phase ( Vargas-Blanco et al, 2019 ).…”
Section: Mrna Stabilization As a Response To Stressmentioning
confidence: 99%
“…An E. coli transcriptome-wide mRNA half-life study by a different group reported that the rate of mRNA degradation had a very weak positive correlation with mRNA abundance for both exponential phase ( R 2 = 0.07) and stationary phase ( R 2 = 0.19) ( Chen et al, 2015 ), in contrast to other E. coli studies ( Bernstein et al, 2002 ; Esquerre et al, 2014 , 2015 ). In Bacillus cereus , mRNA half-life had a positive correlation with expression level ( Kristoffersen et al, 2012 ), while in Stenotrophomonas maltophilia and Chlamydia trachomatis trachoma and lymphogranuloma venereum biovars no correlations were found ( Bernardini and Martinez, 2017 ; Ferreira et al, 2017 ). In M. smegmatis , induced overexpression of dCas9 (in the absence of a gene-targeting sgRNA) did not alter its half-life in log phase ( Vargas-Blanco et al, 2019 ).…”
Section: Mrna Stabilization As a Response To Stressmentioning
confidence: 99%
“…In particular, bacterial metabolism is subjected to several layers of regulation that include transcriptional regulation and mRNA degradation, translational regulation and, once the protein is synthetized, other events of protein modification and activation. Whereas methods for studying at a global level transcriptional regulation and even mRNA degradation are well established 2 4 , and proteomics allows tracking changes at the protein level, simple and standardized methodologies for linking transcriptomics and proteomics in the aim of defining translational changes are not so frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have provided evidence that the CafA homologue in Stenotrophomonas maltophilia has a global role in mRNA stability (Bernardini et al, 2015) and consequently in the regulation of gene expression in this organism. More specifically, CafA was shown to be associated with increased resistance to quinolones and was suggested to be involved in the cellular response to stress (Bernardini et al, 2017). We therefore speculate that the cellular stress induced by the three group IB transition metals may involve post-transcriptional regulation by CafA.…”
Section: Resultsmentioning
confidence: 84%